Impacts of Ethanol Production and Drying Conditions on the Chemical, Physical, and Flowability Properties of Distillers Dried Grains With Solubles - Rosentrater, Kurt A.; Zhang, Yanhong; Wrenn, Brian (Frontiers in Bioengineering and Biotechnology, 2021)
The production of corn-based ethanol in the U.S. has been dramatically increasing in recent years, and consequently so has the quantity of coproduct materials generated from this processing sector. These streams are primarily utilized as livestock feed, which partially offsets the need for corn in feed rations. Because of its use as an animal feed, considerable research has been conducted into the nutritional properties, and to some extent the physical properties, of commercially-available distillers dried grains with solubles (DDGS). There are, however, occasions when the quality of coproducts is not consistent. Thus questions regarding the influence of production operations on the resulting coproduct characteristics must be asked. Toward that end, the objective of this research was to conduct physical and flowability property analyses on DDGS samples which were produced under varying conditions, in order to investigate the effects of various manufacturing operations (specifically ethanol processing and drying conditions) on the resulting properties of the DDGS. Using standard laboratory methods physical properties, including bulk density and angle of repose, were determined. Preliminary results from this study will be presented. The data generated during this study will be useful to both the ethanol and livestock industries, but further study is warranted in order to capture more fully the differences in physical properties due to varying processing conditions, and also to develop quality control techniques to ensure consistent coproduct streams.